Functional divergence between Vachellia and Senegalia could underpin differences in invasiveness and Eltonian niche partitioning in African savannas - Lewis, Joel Robin (Department of Biological Sciences, 2020)
For several decades Vachellia and Senegalia have been assumed to be ecological equivalents in African savannas. Their supposedly close evolutionary relationship has, however, been totally revised in light of recent molecular phylogenetic data. These data highlight the deep divergence (± 30 Ma) between these genera and also their independent transitions into African savannas. Distant divergence and independent transitions into savannas between Vachellia and Senegalia suggest their possible ecological niche divergence, which could explain the observed differences in invasiveness between them. This thesis provides the first ecophylogenetic study to assess the level of ecological niche divergence between these economically, socioeconomically and ecologically important tree genera in Africa. I address this question by first determining the scale(s) of coexistence between Vachellia and Senegalia and determine their phylogenetic community structure at both the landscape-regional scale and the plot-scale. I then conduct a large glasshouse experiment using seven species from each genus to determine conserved functional differences between them during seedling establishment in the presence, and also the absence, of grass competition. While I find evidence of some Grinnellian niche differentiation between Vachellia and Senegalia at the landscape-regional scale, their greater-than-expected co-occurrence in plots suggests they generally partition an Eltonian niche in savannas. Glasshouse trait data also reveal that Vachellia has a conserved strategy for rapid vertical growth when free from grass competition and Senegalia has a conserved root tissue density response to grass competition. I argue that the rapid growth (bolting) strategy of Vachellia in the absence of grass competition provides a functional explanation for why this genus is observed to be relatively more invasive in grassy ecosystems. I also argue that the root tissue density response of Senegalia enables stable coexistence at the plot scale with Vachellia as it increases competitive ability among grasses leaving establishment less tied to times of low grass biomass. I conclude that this study provides overwhelming support for ecological niche divergence between Vachellia and Senegalia and that this divergence may underpin their observed differences in invasiveness. That the coexistence of these genera is largely attributable to Eltonian niche partitioning also provides fresh support for the contention that tree-tree competition structures tree communities in African savannas. Finally, niche divergence suggests that, when promoting diversity and managing invasion, Vachellia and Senegalia species will require different management practices.